Orientalist Construction on the Existence of Ammiyah Arabic in Egypt in the 20th Century - M. Taufiq Hidayat Pabbajah; Mustaqim Pabbajah (Institut Agama Islam Negeri (IAIN) Kendari, 2020)
This study aims to explorehow the Ammiyah language came about in Egypt in the 20th century. It adopted an observational research design. To gather the data, the books and journals covering Orientalism were examined.The study details three of the findings. First, the Ammiyah language differs from the Arabic Fusha in terms of syntax, lexical and phonological characteristics. Second, Ammiyah has often been used in Egypt in familial and social communication. Third, the construction carried out by Orientalists in popularizing the Ammiyah language in order to shift the role of the Arabic Fusha as the language of state administration in Egypt through two aspects. The government orders the writing of books and newspapers in the Ammiyah language using Latin letters, and prohibits the teaching of Fusha language in the school and all activities. Although the Orientalist effort failed because of the opposition from Arab literary groups both Muslim and Christian Arabs, as well as the Al-Azhar and Majma 'Lughah Universities which protected the purity of the Arabic language, there was still a social impact on Egyptian society. The Egyptian society utilizes a number of Ammiyah languages in day-to-day contact.